化简 (sin2x)/(1+cos2x)*(cosx)/(1+cosx)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 12:57:28
化简(sin2x)/(1+cos2x)*(cosx)/(1+cosx)化简(sin2x)/(1+cos2x)*(cosx)/(1+cosx)化简(sin2x)/(1+cos2x)*(cosx)/(1+
化简 (sin2x)/(1+cos2x)*(cosx)/(1+cosx)
化简 (sin2x)/(1+cos2x)*(cosx)/(1+cosx)
化简 (sin2x)/(1+cos2x)*(cosx)/(1+cosx)
cos2x=cosx*cosx-sinx*sinx=1-2*sinx*sinx;
sin2x=2*sinx*cosx;
所以(sin2x)/(1+cos2x)*(cosx)/(1+cosx)
=(2*sinx*cosx)/(1+(1-2*sinx*sinx))*(cosx)/(1+cosx)
=(2*sinx*cosx)/2(1-sinx*sinx)*(cosx)/(1+cosx)
=(2*sinx*cosx)/(2cosx*cosx)*(cosx)/(1+cosx)
=sinx/cosx*(cosx)/(1+cosx)
=sinx/(1+cosx)
答案:tan(x/2)
化简 (1+sin2x-cos2x)/(1+sin2x+cos2x)
化简(cos2x-sin2x)/(1-cos2x)(1-tan2x)
(1+ sin2x)/(1+ cos2x+ sin2x)化简
化简(1+sin2x)/(1+sin2x+cos2x)
化简[1+SIN2X-COS2X]/[1+SIN2X+COS2X]的结果
化简:cos2x/(1-sin2x)
sin2x/(1-cos2x)-(1/tanx) 化简
化简 (sin2x)/(1+cos2x)*(cosx)/(1+cosx)
sin2x+cos2x+1/1+tanx 化简
化简:(sinx+sin2x)/(1+sinx+cos2x)
化简:(sinx+sin2x)/(1+cosx+cos2x)
化简sin2x+cos2x
sin2x·cos2x化简
sin2x×cos2x/2,化简.
化简cos2x*sin2x
1-cos2x+sin2x=
(1+sin2x-cos2x)/(1+sin2x+cosx)
求证1+sin2x-cos2x/1+sin2x+cos2x=tanx